Pollution and Environmental Factors Effect on Calcification and Morphology of Mytilus galloprovincialis Shell from El Jadida Coast (Atlantic Coast, Morocco) - Khalil, Amine; Sif, Jamila; Kabriti, Mohamed (Trends in Sciences, 2022)
The originality of the present work is to study, for the 1st time, the existence of shell shape deformation in Mytilus galloprovincialis mussel from Morocco Atlantic coasts, in relation with local environmental parameters. A slight difference is noted in the average calcium concentrations between the 2 sites, with values of 10.02⸱10–2 ± 0.15 mM and 10.3⸱10–2 ± 0.15 mM respectively at Haouzia and Jorf-Lasfar sites. A significant season al variation was observed in both sites, with the existence of 2 concentration peaks during the months of April and September. These results are correlated with the physicochemical records with the existence of a salinity gradient. Shell deformation was observed in 25.9 % of all individuals from Jorf-Lasfar site. These individuals (group 2) show a higher concentration of calcium ions in their shells, a reduced width and increased thickness. HIGHLIGHTS Due to increasing pressure of pollution and environmental factors on mussels from morocco coastal line, our research team investigated disturbance on shell shape by carrying out morphometric and calcium ions titration study: At a morphometric level, we found that individuals with shell deformity lose width and gain thickness At a physiological level, these individuals have an increased amount of calcium ions in the shell compared to mussels with no shell deformation Suspected effect of environmental parameters on Mytilus galloprovincialis physiology GRAPHICAL ABSTRACT